Metode Qiro’ati: Implementasinya dalam Pembelajaran Membaca Al-Qur’an di Taman Pendidikan Al-Qur’an - Hasanah, Uswatun; Jamilah, Jamilah; Rapiko, Rapiko; Fitrianda, J.M Eka; Hamdan, Hamdan; Takriyanti, Rizky (ISLAMIC PEDAGOGY: Journal of Islamic Education, 2024)
The study aims to understand the implementation of the Qiroati method in Quranic reading education for Volume IV at Raudhotut Taqwa Quranic Education Garden in Pasar Singkut Village, Sarolangun Regency. This qualitative research employs a descriptive analysis approach and was conducted at Raudhotut Taqwa Quranic Education Garden in Pasar Singkut Village, Sarolangun Regency. Data sources include primary data from caregivers, Ustadzah (female Islamic teacher) of Volume IV, and students of Volume IV at Raudhotut Taqwa Quranic Education Garden, and secondary data regarding the conditions of Raudhotut Taqwa Quranic Education Garden in Pasar Singkut Village, Sarolangun Regency. Data collection methods used were observation, interviews, and documentation. The collected data were analyzed using data reduction techniques, data presentation, and verification of conclusions drawn. The research found that the implementation of the Qiroati method in Quranic reading education at Raudhotut Taqwa Quranic Education Garden in Pasar Singkut Village, Sarolangun Regency, adheres well to the specified Qiroati method. The Quranic education process for Volume IV students at Raudhotut Taqwa Quranic Education Garden aligns with the guidance of the Qiroati method, with the materials learned corresponding to the directions provided on each page of the Volume IV book.